Isolation, characterization, and biological properties of a tuberculin-active peptidoglycan isolated from the culture filtrate of Mycobacterium tuberculosis. - Gupta, K C (1980)
A water-soluble tuberculin-active peptidoglycan (TAPG) with a molecular weight of ca. 28,000 to 30,000 was isolated from the culture filtrate of Mycobacterium tuberculosis. TAPG was approximately four to five times more potent than tuberculin purified protein derivative S in guinea pigs sensitized with M. tuberculosis or M. bovis (freeze-dried BCG). It showed little or no cross-reactivity at a dose of 0.1 to 0.4 microgram in guinea pigs sensitized with M. kansasii, M. scrofulaceum, M. intracellulare, or M. avium. TAPG did not show any adjuvant activity when injected in guinea pigs in a water-in-oil emulsion containing ovalbumin. TAPG, in Freund incomplete adjuvant, proved to be an effective immunogen for inducing delayed hypersensitivity in guinea pigs. Chemical analysis of TAPG showed that it contains proline, glutamic acid, alanine, diaminopimelic acid, tyrosine, threonine, glucosamine, and the reducing sugars, arabinose and galactose. In immunoelectrophoretic studies with reference M. tuberculosis H37Rv antiserum, TAPG did not show any precipitin bands.